Transcriptome analysis of immune responses in Macrobrachium rosenbergii against white spot syndrome virus and Vibrio parahaemolyticus / Ramarao Seriramalu - Ramarao , Seriramalu (2017)
The Malaysian giant freshwater prawn, Macrobrachium rosenbergii, an economically important crustacean worldwide are being affected by pathogens such as the white spot syndrome virus (WSSV) and Vibrio species. The information regarding the regulation of innate immune system in this species is lacking, however it is critical in providing solutions to control and minimize the loss of production due to diseases. An investigation regarding immune response of M. rosenbergii towards V. parahaemolyticus and WSSV infection were undertaken by performing a transcriptome profiling of M. rosenbergii hepatopancreas infected with these two pathogens by using the ‘Next Generation’ sequencing method (Illumina HiSeqTM2000). The reads were assembled de novo and were annotated against databases using the BLASTX search (E-value <10-5). A total of 22,455 unigenes (34.86% of all unigenes) were successfully annotated. The unigene differential expression analysis by FPKM (Fragments Per kb per Million fragments) method revealed 14,569 unigenes that were differentially expressed in Vibro-infected shrimp and 14,416 in WSSV-infected ones when compared to the controls. Several differentially expressed unigenes were shown to be involved in various animal immune functions. Interestingly, we also found 79 immune related unigenes that were up-regulated in M. rosenbergii when independently infected with each of the pathogen. Among those unigenes is the STAT gene, a key component of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. We further characterised the full-length cDNA of STAT (designated as MrSTAT) obtained from the transcriptome database by using various bioinformatics tools. Time course analysis of the transcription level of MrSTAT in hepatopancreas after WSSV and V.parahaemolyticus challenge showed significant (p < 0.05) increase expression, highest are at 6 hours for WSSV- infected and 24 hour for V.parahaemolyticus- infected ones. All these results may imply the potential role of JAK/STAT pathway in the immune response against bacteria and virus in M. rosenbergii.